2020
DOI: 10.1021/acs.chemrev.0c00062
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Transition-Metal-Catalyzed [2 + 2 + 2] Cycloaddition Reactions

Abstract: The development of catalytic methodologies involving the formation of C−C bonds to enable the generation of cyclic systems constitutes a field of great relevance in synthetic organic chemistry. One paradigmatic process to accomplish this goal efficiently is the transition-metal-catalyzed [2 + 2 + 2] cycloaddition reaction, since it permits the formation of a wide range of highly functionalized 6-membered carbo-and heterocyclic molecules in a single step with high efficiency and perfect atom economy. A key feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 410 publications
3
106
0
1
Order By: Relevance
“…On the basis of the above results and previous reports, [8d,11a,12] two types of proposed mechanisms for the cobalt‐catalyzed [2+2+2] cycloaddition of the fluoroalkylated diynes 2 with nitriles 1 are depicted in Scheme 4 [13] . Thus, the cobalt(II) catalyst is reduced by Zn/ZnBr 2 system to generate the cobalt(I) active species [14] .…”
Section: Resultsmentioning
confidence: 58%
“…On the basis of the above results and previous reports, [8d,11a,12] two types of proposed mechanisms for the cobalt‐catalyzed [2+2+2] cycloaddition of the fluoroalkylated diynes 2 with nitriles 1 are depicted in Scheme 4 [13] . Thus, the cobalt(II) catalyst is reduced by Zn/ZnBr 2 system to generate the cobalt(I) active species [14] .…”
Section: Resultsmentioning
confidence: 58%
“…The multicomponent synthesis of pyridines has been extensively studied, in particular strategies involving the formal [2 + 2 + 2] cycloaddition of alkynes and nitriles. 11,13,22,[69][70][71][72][73][74] This topic has been the subject of numerous recent reviews, so this perspective will focus primarily on comparing and contrasting mechanistic and scope aspects of the group 4-8 catalysts. In the context of group 4-8 metal-catalyzed [2 + 2 + 2] syntheses, methods are primarily dominated by Ru and Fe, although there are several emergent examples with group 4 and 5 that suggest they may have unrealized potential for pyridine synthesis as well.…”
Section: Pyridinesmentioning
confidence: 99%
“…Compared to other transition metals, Ru-based catalysts provide complementary access to pyridines with electron-decient nitriles, [80][81][82] which are oen challenging substrates for later transition metals like Co. 83 In contrast, cycloaddition using simple nitriles such as MeCN and PhCN is challenging with Ru due to oen endothermic nitrile insertion, 81 although examples of partially or fully intermolecular [2 + 2 + 2] cycloaddition with nitriles containing coordinating groups have been reported. 81,84,85 Detailed experimental and computational studies (both of [2 + 2 + 2] alkyne cyclotrimerization and pyridine formation) 22,86 have revealed that Cp*RuCl(COD)-catalyzed reactions of a,udiynes likely proceed rst through initial oxidative cyclization of the diyne to form ruthenacyclic biscarbenoid IM32. This intermediate, which related complexes have been structurally characterized via X-ray crystallography and NMR in several instances, 87 is shared between [2 + 2 + 2] pyridine formation, alkyne cyclotrimerization, and [2 + 2 + 1] pyrrole/furan/ thiophene synthesis (vide supra).…”
Section: Pyridinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] In addition to these synthetic advantages, the transition‐metal‐catalyzed alkyne [2+2+2] cycloaddition has also attracted considerable attention from a mechanistic point of view. [ 3 ] Based on the isolation of metallacyclopentadiene intermediates, Shore proposed the so‐called “common mechanism”, illustrated in Scheme 1a. [ 4 ] Bis(alkyne) complex A undergoes oxidative coupling (OC) to produce metallacyclopentadiene intermediate B .…”
Section: Introductionmentioning
confidence: 99%